The diagnosis and treatment of retrograde intussusception: a single-centre experience - Bing Zhang (BMC, 2021)
Abstract Background/Purpose To investigate the clinical manifestations, treatments of retrograde intussusception and summarize the experience. Methods Children with retrograde intussusception treated in our hospital from January 2011 to January 2021 were retrospectively analysed. Demographics, clinical manifestations, preoperative colour Doppler ultrasound (CDU) findings, findings during surgery and follow-up results were collected. Results A total of 4719 cases of intussusception were treated in our department, including 12 cases of retrograde intussusception (0.25%). There were 8 males and 4 females.The age ranged from 4.1 to 14.3 months, with an average of (8.3 ± 2.8) months.; The weight ranged from 5.5 to 12.6 kg, with an average of (9.4 ± 2.3) kg; The onset time ranged from 6 to 15 h, with an average of (10.0 ± 2.4) h. All the children received CDU examination before surgery, and in one case, the possibility of 2 intussusception masses was considered. Emergency surgical exploration was performed after the failure of air enema reduction. During the operation, multiple types of intussusception were found (coincidence of anterograde and retrograde intussusception). The pattern of anterograde intussusception was all ileo-ileo-colic variety and the retrograde intussusception was proximal sigmoid colon into descending colon. All the children were successfully reduced by manual reduction without intestinal necrosis or intestinal malformation. All children were discharged 6–7 days after surgery, and had no recurrence after 3–6 months of follow-up. Conclusions Retrograde intussusception is easily misdiagnosed before surgery. During air enema, if the intussusception mass was fixed and did not move with increasing pressure, we should be aware of the possibility of retrograde intussusception, and the enema pressure should not be too large to avoid intestinal perforation. If the intraoperative position of the intussusception mass was not consistent with that of the preoperative enema, it was recommended to use bimanual examination to explore whether there was still a mass in the abdominal cavity to avoid misdiagnosis.